MODELLING AND NN CONTROL OF A TWO-LINK FLEXIBLE ROBOT MANIPULATOR - Khairudin, Mohammad (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
This paper presents investigations into the development of neural network (NN) control of a two-link flexible robot manipulator with load 0.5 kg. A dynamic model of the system is derived using a combined Euler-Lagrange and assumed mode methods (AMM). The controller reduces nonlinearities problem that can be efficiently solved using NN control. The system responses namely hub angular position and deflection responses and end-point acceleration at both links are obtained and analysed. The performances of the controllers are assessed in terms of the input tracking controller capability of the system. Moreover, the robustness of the NN control schemes is discussed. Finally, a comparative assessment of the control strategies is presented. The results show that NN controller performs give increasing profiles that compared with PID control.